2012
DOI: 10.1007/s00217-012-1733-8
|View full text |Cite
|
Sign up to set email alerts
|

Current enzymatic milk fermentation procedures

Abstract: Aside from bacteria, yeasts and moulds, enzymes from animal, vegetal and microbial sources are increasingly utilized for milk fermentation providing a broad spectrum of innovative product conceptions. In order to alter texture and flavour or to improve the nutritional value of milk-based products from different animal milks, microbial and enzymatic fermentation procedures are traditionally established worldwide. To date, genomic and proteomic approaches enable new selection strategies for precise enzymes for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…It reported that cheese coagulation by chymosin is slower and weaker in camel compared to bovine milk ( 3 ) but the mechanisms behind these differences are still not known. In bovine milk, chymosin hydrolysis of κ-casein is the most important proteolytic reaction during cheese making ( 78 ). Of the rennet used in bovine milk coagulation, about 6–10% is retained in the bovine cheese curd ( 79 ) but the residues chymosin retained in camel cheese curd to further hydrolyze other caseins requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…It reported that cheese coagulation by chymosin is slower and weaker in camel compared to bovine milk ( 3 ) but the mechanisms behind these differences are still not known. In bovine milk, chymosin hydrolysis of κ-casein is the most important proteolytic reaction during cheese making ( 78 ). Of the rennet used in bovine milk coagulation, about 6–10% is retained in the bovine cheese curd ( 79 ) but the residues chymosin retained in camel cheese curd to further hydrolyze other caseins requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Some novel technologies have been developed or applied to improve yoghurt quality at molecular level of milk proteins, for example, by forming covalent bonds between or within the molecules with enzymes (Faegemand, Sørenson, Jørgensen, Budolfsen, & Qvist, 1999). Transglutaminase (TGase, EC 2.3.2.13) is one of typical enzymes capable of forming isopeptide bonds between the γ-carboxyamide groups and the amino groups and thus can be used to induce cross-linking of food proteins (Beermann & Hartung, 2012;Lorenzen, Neve, Mautner, & Schlimme, 2002) or glycosylation plus cross-linking of casein or soybean proteins (Jiang & Zhao, 2010. The influences of TGase treatment on functional properties of milk proteins had been widely studied (Faegemand & Qvist, 1997;Hiller & Lorenzen, 2009), while the impacts of TGase treatment on the textural and other attributes of yoghurt products were also well characterized (Bönisch, Huss, Weitl, & Kulozik, 2007;Lorenzen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The rennet enzymes are aspartic peptidase, and the most used are the combinations of chymosin A, B, C, and pepsin extracted from the stomach of calves and other ruminants ( 131 ). Renins disrupt the milk emulsion and separate caseins from the whey, causing them to coagulate into cheese by cleaving κ-casein into para-κ-casein and casein macropeptide ( 132 , 133 ). Many studies have consistently found that the coagulation of CM proceeds at much lower rates and produces a more fragile coagulum compared to BM when using bovine chymosin ( 125 , 134 – 137 ).…”
Section: Effect Of Coagulantsmentioning
confidence: 99%